Воєнно-політична експансія більшовицької Росії на західні землі України в 1919–1923 рр. - Литвин, М. (Український історичний журнал, 2022)
Мета дослідження – розглянути особливості зовнішньої політики більшовицької
Росії щодо західних земель України після Першої світової війни, насамперед у
період Західноукраїнської Народної Республіки, і в наступні роки (листопад 1918 – березень
1923 рр.). Використано загальнонаукові та спеціальні історичні методи: причинно-наслідковий,
історико-порівняльний, історико-топологічний, історико-генетичний, системного аналізу.
Наукова новизна полягає в розкритті планів Кремля щодо розвитку сепаратистських
настроїв серед галичан, спрямованих проти ЗУНР, загалом соборної Української Народної
Республіки, які мали реалізовуватися шляхом проголошення маріонеткової Галицької
Соціалістичної Радянської Республіки зі столицею у Львові. Основні результати дослідження. Акцентовано увагу на творенні центрального тимчасового органу влади – Галицького
ревкому на чолі з В.Затонським та ЦК Комуністичної партії Східної Галичини, які було
узгоджено з головою Ради народних комісарів В.Леніним, ЦК Російської комуністичної
партії (більшовиків) і ЦК Комуністичної партії (більшовиків) України. Стверджено, що нові
центральні й місцеві органи формувалися за участі та підтримки командирів, політкомісарів
Південно-Західного фронту, одним з яких був Й.Сталін. Місцеві ревкоми проводили
суботники й недільники, організовували експропріацію збіжжя у землевласників, грошей,
коштовностей у заможних поляків та євреїв, намагалися реорганізувати за більшовицьким
зразком заклади освіти. Здійснювався тиск на греко-католицькі церковні громади, священнослужителів.
До «радянського будівництва» влада намагалася залучити зубожілих селян і
міщан, громадян лівих поглядів, представників радянофільських структур, вояків Червоної
української галицької армії, котрі поверталися до рідних домівок улітку 1920 р. Висновки.
«Визвольний похід» більшовиків на Східну Галичину та у Центрально-Східну Європу було
зупинено збройним спротивом об’єднаного польсько-українського війська під Львовом,
Замостям, на берегах Дністра. Після відступу червоних за Збруч у вересні 1920 р. Раднарком
Росії, ЦК РКП(б), ЦК КП(б)У намагалися насаджувати комуністичні ідеї за допомогою
структур Закордоту, осередків КПСГ, шляхом дискредитації діячів ЗУНР, навернення до
радянофільства її керманича Є.Петрушевича. The purpose of the study – to investigate the peculiarities of the foreign policy of
Bolshevik Russia towards the western lands of Ukraine after the World War I, primarily in the
period of the West Ukrainian People’s Republic and then (November 1918 – March 1923). In
the course of work are used general scientific and special historical methods of research: causal,
historical-comparative, historical-topological, historical-genetic, system analysis, etc. The scientific
novelty is the revelation of the Kremlin’s plans to instil in Halychyna separatist sentiments to the
West Ukrainian People’s Republic, to the conciliar Ukrainian People’s Republic, which were to
be realized through the proclamation of the puppet Halychyna Socialist Soviet Republic (HSRR;
August – September 1920). The main results of the study. Emphasis is placed on the creation
of the Central Provisional Authority of the HSSR – Halychyna Revolutionary Committee headed
by V.Zatonskyi and the Central Committee of the Communist Party of Eastern Halychyna, which
were agreed with the chairman of the Russian Council of People’s Commissars V.Lenin, the
Central Committee of the Russian Communist Party (Bolsheviks) and the Communist Central
Committee (Bolsheviks) of Ukraine. It is claimed that the new central and local authorities
were formed with the participation and support of brigade and regimental commanders,
political commissars of the South-Western Front, one of whose commanders was J.Stalin. Local
Revolutionary Committees held subbotniks and voskresniks, organized the expropriation of grain
from landowners, money and valuables from wealthy Poles and Jews, and tried to reorganize
educational institutions on the Bolshevik model; pressure was exerted on church communities
and clergy of the Ukrainian Greek Catholic Church. The authorities tried to involve impoverished
peasants and burghers, left-wing citizens, representatives of Moscow structures, and recent soldiers
of the Red Ukrainian Halychyna Army who were returning to their native homes in the summer
of 1920. Conclusions. The “liberation campaign” of the Red Army in Eastern Halychyna, and
then in Central and Eastern Europe, was stopped by the armed resistance of the united Polish-
Ukrainian army near Lviv and Zamość, on the banks of the Dnister. After the retreat of the Red
Army behind Zbruch in September 1920, the Soviet People’s Commissar of Bolshevik Russia, the
Central Committee of the RCP(B), and the Central Committee of the CP(B)U tried to instil
Bolshevik ideas with the help of Zakordot structures, cells of the Communist Party of Eastern
Halychyna, by discrediting the figures of the Western Ukrainian People’s Republic, converting to
Soviet ideology Ye.Petrushevych.